2019
DOI: 10.4103/1673-5374.255980
|View full text |Cite
|
Sign up to set email alerts
|

L-Norvaline, a new therapeutic agent against Alzheimer’s disease

Abstract: Growing evidence highlights the role of arginase activity in the manifestation of Alzheimer’s disease (AD). Upregulation of arginase was shown to contribute to neurodegeneration. Regulation of arginase activity appears to be a promising approach for interfering with the pathogenesis of AD. Therefore, the enzyme represents a novel therapeutic target. In this study, we administered an arginase inhibitor, L-norvaline (250 mg/L), for 2.5 months to a triple-transgenic model (3×Tg-AD) harboring PS1M146V, APPSwe, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 87 publications
3
44
0
Order By: Relevance
“…L-norvaline treatment leads to a drop in the microglia density in the hippocampi of Alzheimer's disease model mice, which is followed by a shift from activated to resting microglial phenotype [35]. Additionally, L-norvaline significantly reduces the brain levels of TNFα in the same murine model [40]. Therefore, its application in the models of hypertension might have a particular benefit.…”
Section: Discussionmentioning
confidence: 99%
“…L-norvaline treatment leads to a drop in the microglia density in the hippocampi of Alzheimer's disease model mice, which is followed by a shift from activated to resting microglial phenotype [35]. Additionally, L-norvaline significantly reduces the brain levels of TNFα in the same murine model [40]. Therefore, its application in the models of hypertension might have a particular benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the administration of VEGF in rats with focal cerebral ischemia reduces the infarct size and enhances neurogenesis [25]. 4 Likewise, we disclosed that norvaline treatment led to a significant increase in the levels of the glial cell-derived neurotrophic factor (GDNF) receptor RET (REarranged during Transfection) [15], which is a common signaling receptor for GDNF-family ligands [26]. Of note, GDNF is down-regulated in 3×Tg mice [27], and its overexpression improves cognitive function in this AD model [28].…”
mentioning
confidence: 97%
“…These authors demonstrated that NOS1 repression decreases neuronal differentiation, and vice versa, NOS1 upregulation promotes it.The semi-essential amino acid, arginine, is a mutual substrate for both NOS and arginase. Brain arginine deprivation, due to arginase over-activation, has been suggested as a cause of AD [12].Consequently, arginine supplementation [13] and/or arginase inhibition have been proposed to halt AD development [14], and have been successfully tested in AD mice [15]. Previously, we showed that arginase inhibition with norvaline upsurges the hippocampal levels of NOS3 [16], and NOS1[17] in AD model mice.Additionally, our advanced proteomics assay revealed that chronic treatment of 3×Tg mice with norvaline led to the activation of several critical for adult neurogenesis biological processes [15].One of the most significant pathways detected was the neuregulin (NRG) pathway.…”
mentioning
confidence: 99%
See 2 more Smart Citations